AN ESSAY ON THE LIBERAL-SOCIAL FOUNDATIONS OF THE BRAZILIAN CONSTITUTION OF 1988 - Copetti Neto, Alfredo (2017)
In this article, it is sought to show that the defense of the constitution and the rule of law has a purpose that is not internal, but external, for the sake of the nation, which shifts the concern of the constituent for a social and economic development project. Taking into account the postulate of the substantive legality, the separation and division of powers, and the individual and social rights guarantees, it is found that the Federal Constitution of 1988 establishes mechanisms that prevent or hinder the abuse and arbitrary and illegitimate exercise of power, forecasting the duties of State performance in the economic sphere, so that the principles of the economic order are observed. The importance of this study justifies itself, in a way that if the discussion about the philosophical and political foundations of the Brazilian Constitution does not occur in a serious way, the traditional dilemma surrounding the debate about the concept of economic constitution will persist. Transversely following this confusion, it will be found the contemporary politic positions adopted on civil liberties, that undermine and distort the republican and laic foundations of the state and the Law.